Ionosphere variability I: Advances in observational, monitoring and detection capabilities - Ioanna Tsagouri; Anna Belehaki; David R. Themens; Norbert Jakowski; Tim Fuller-Rowell; Mainul M. Hoque; Grzegorz Nykiel; Wojciech J. Miloch; Claudia Borries; Anna Morozova; Teresa Barata; William Engelke; et al. (Advances in Space Research, 2023)

Herbivory and dominance shifts among exotic and congeneric native plant species during plant community establishment - Tim Engelkes; Annelein Meisner; Elly Morriën; Olga Kostenko; Wim H. Van der Putten; Mirka Macel (Oecologia, 2016)

A fast-track for invasion: invasive plants promote the performance of an invasive herbivore - Tim Engelkes; Nicholas J. Mills (Biological Invasions, 2013)

A conceptual framework for understanding arthropod predator and parasitoid invasions - Tim Engelkes; Nicholas J. Mills (BioControl, 2011)

Additive effects of aboveground polyphagous herbivores and soil feedback in native and range‐expanding exotic plants - Elly Morriën; Tim Engelkes; Wim H. van der Putten (Ecology, 2011)
Plant biomass and plant abundance can be controlled by aboveground and belowground natural enemies. However, little is known about how the aboveground and belowground enemy effects may add up. We exposed 15 plant species to aboveground polyphagous insect herbivores and feedback effects from the soil community alone, as well as in combination. We envisaged three possibilities: additive, synergistic, or antagonistic effects of the aboveground and belowground enemies on plant biomass. In our analysis, we included native and phylogenetically related range‐expanding exotic plant species, because exotic plants on average are less sensitive to aboveground herbivores and soil feedback than related natives. Thus, we examined if lower sensitivity of exotic plant species to enemies also alters aboveground‐belowground interactions. In a greenhouse experiment, we exposed six exotic and nine native plant species to feedback from their own soil communities, aboveground herbivory by polyphagous insects, or a combination of soil feedback and aboveground insects and compared shoot and root biomass to control plants without aboveground and belowground enemies. We observed that for both native and range‐expanding exotic plant species effects of insect herbivory aboveground and soil feedback added up linearly, instead of enforcing or counteracting each other. However, there was no correlation between the strength of aboveground herbivory and soil feedback. We conclude that effects of polyphagous aboveground herbivorous insects and soil feedback add up both in the case of native and related range‐expanding exotic plant species, but that aboveground herbivory effects may not necessarily predict the strengths of soil feedback effects.

Ecological fits, mis-fits and lotteries involving insect herbivores on the invasive plant, Bunias orientalis - Jeffrey A. Harvey; Arjen Biere; Taiadjana Fortuna; Louise E. M. Vet; Tim Engelkes; Elly Morriën; Rieta Gols; Koen Verhoeven; Heiko Vogel; Mirka Macel; Hanna M. Heidel-Fischer; Katharina Schramm; et al. (Biological Invasions, 2010)